Effects of Marangoni convection on the embedding dynamic behavior of SiC nano-particles into the Al molten pool during laser micro-melting. (5th April 2018) - Cui, C.Y.; Li, X.D.; Fang, C.; Zhang, W.L.; Ruan, Z.W.; Cui, X.G.; Lu, J.Z.; Xia, C.D.; Lu, Y.F.
Abstract: A facile approach to fabricate a surface nanocomposite structure by embedding SiC nano-particles (NPs) via laser micro-melting is reported. A high fidelity model is adopted to reveal transient temperature distributions and the embedding of the SiC NPs into an Al molten pool during laser micro-melting. Special attention is paid to the embedding dynamic behaviours within the molten pool affected by Marangoni convection. Fluid flow and migration characteristics of the SiC NPs into the molten pool, as well as the resultant bubble motion and pore defects formation, are considered. Simulation results show that the temperature distribution is basically symmetrical with respect to the laser beam, and the Marangoni convection in the molten pool tends to embed the SiC NPs into the Al surface layer together with gas bubbles. This phenomneon is well validated by the experimental study on the surface morphology and the SiC NPs distribution in the Al surface layer. Microstructural characterizations indicate that a relatively flat reinforced SiC/Al surface can be formed at an optimized laser energy of 0.6 J. These studies may provide a new strategy for constructing nanocomposite structure on metal alloy surface. Graphical abstract: Highlights: SiC nano-particles are embedded into Al molten pool based on laser micro-melting. Embedding behavior of nano-particles into Al molten pool is simulated by FLUENT. Experimental studies are carried out to verify the simulated results.